Post a New Question

algebra 2

posted by .

Solve the system using substitution.
Y=-3x^2+x-2,
Y=-5x+3

  • algebra 2 -

    -5x+3 = -3x^2+x-2

    Add 5x and subtract 3 from both sides of the equation. Multiply both sides by -1.

    0 = 3x^2 - 6x + 5

    However, I don't see how this can be factored. Do you have a typo?

  • algebra 2 -

    Solving nonlinear systems

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question